2005
DOI: 10.1074/jbc.m502173200
|View full text |Cite
|
Sign up to set email alerts
|

Coactivator-associated Arginine Methyltransferase 1, CARM1, Affects Pre-mRNA Splicing in an Isoform-specific Manner*♦

Abstract: Molecular diversity through alternative splicing is important for cellular function and development. However, little is known about the factors that regulate alternative splicing. Here we demonstrate that one isoform of coactivator-associated arginine methyltransferase 1 (named CARM1-v3) associates with the U1 small nuclear RNP-specific protein U1C and affects 5 splice site selection of the pre-mRNA splicing. CARM1-v3 was generated by the retention of introns 15 and 16 of the primary transcript of CARM1. Its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 33 publications
1
75
0
1
Order By: Relevance
“…In addition to PRMT1, alternative splicing was also reported for CARM1 and PRMT7 pre-mRNAs (77,78), although extensive biochemical characterization of the respective PRMT isoforms generated is still lacking. As we have shown in the current study, alternative splicing can lead to the production of PRMT variants with a wide array of different biochemical and regulatory properties.…”
Section: Complex Genomic Structure At the 5ј-end Of The Prmt1 Gene Lementioning
confidence: 99%
“…In addition to PRMT1, alternative splicing was also reported for CARM1 and PRMT7 pre-mRNAs (77,78), although extensive biochemical characterization of the respective PRMT isoforms generated is still lacking. As we have shown in the current study, alternative splicing can lead to the production of PRMT variants with a wide array of different biochemical and regulatory properties.…”
Section: Complex Genomic Structure At the 5ј-end Of The Prmt1 Gene Lementioning
confidence: 99%
“…PAF1c functions in transcription initiation, elongation (15), mRNA 3′ end cleavage (25), polyadenylation of mRNA precursors (27), and small nucleolar RNA (snoRNA) 3′ end formation (31). In addition to transcriptional activation, CARM1 methylates splicing factors (32), modulates recognition of 5′ splicing sites (33), and regulates the coupling of transcription and splicing (34). Furthermore, a recent report showed that RNAPII carboxyl-terminal domain is methylated by CARM1 (35).…”
Section: Paf1c and Carm1 Coordinately Regulate A Common Set Of Erαmentioning
confidence: 99%
“…The underlined sequences form a stem region of CARM1 shRNA which corresponds to 229 to 247 nucleotides of rat CARM1. This sequence is shared by all of the reported splicing variants of rat CARM1 (51). To generate stable cell lines, neomycin-resistant gene cassettes should be added to pSILENCER-shCARM1 by recloning BamHI-XbaI digested fragments containing the U6 promoter and CARM1 shRNA sequence into pcDNA3.1 vector with BglII and XbaI sites (pSILENCER-shCARM1 Neo r ).…”
Section: Chemicals and Antibodiesmentioning
confidence: 99%